Ultrafast ignition with relativistic shock waves induced by high power lasers. (1st June 2014) - Eliezer, Shalom; Nissim, Noaz; Vinikman Pinhasi, Shirly; Raicher, Erez; Maria Martinez Val, JosÃ©
Abstract In this paper we consider laser intensities greater than <alternatives><inline-graphic xlink:href="ark:/27927/pgj449htvg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let \leq =\leqslant \let \ge =\geqslant \let \geq =\geqslant \def \Pr {\mathit {Pr}}\def \Fr {\mathit {Fr}}\def \Rey {\mathit {Re}}10^{16}\ \mathrm{W\ cm}^{-2}$]]> </alternatives> where the ablation pressure is negligible in comparison with the radiation pressure. The radiation pressure is caused by the ponderomotive force acting mainly on the electrons that are separated from the ions to create a double layer (DL). This DL is accelerated into the target, like a piston that pushes the matter in such a way that a shock wave is created. Here we discuss two novel ideas. Firstly, the transition domain between the relativistic and non-relativistic laser-induced shock waves. Our solution is based on relativistic hydrodynamics also for the above transition domain. The relativistic shock wave parameters, such as compression, pressure, shock wave and particle flow velocities, sound velocity and rarefaction wave velocity in the compressed target, and temperature are calculated. Secondly, we would like to use this transition domain for shock-wave-induced ultrafast ignition of a pre-compressed target. The laser parameters for these purposes are calculated and the main advantages of this scheme are described. If this scheme is successful a new source of energy in large quantities may become feasible.